2017
DOI: 10.1007/s13205-017-0985-1
|View full text |Cite
|
Sign up to set email alerts
|

Physiological growth and galactose utilization by dairy yeast Kluyveromyces marxianus in mixed sugars and whey during fermentation

Abstract: The dairy yeast represents a promising industrial strain useful for the production of bioethanol from cheese whey. Physiology of the five strains on galactose was examined during batch cultivation under controlled aerobic conditions on minimal media and one of the strains designated strain 6C17 which presented the highest specific galactose consumption rate. A maximum specific growth rate of 0.34 and 0.37 h, respectively, was achieved using batch cultivation in a minimal medium and a complex medium amended wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 32 publications
1
15
0
Order By: Relevance
“…marxianus, an interesting yeast in biotechnology, has been regularly isolated from dairy products due to its ability to assimilate a wide range of sugars, such as lactose. Beniwal et al [49] reported K. marxianus 6C17 ability to hydrolyze galactose into ethanol, thus verifying its variability in sugar fermentation and thereby its alignment with Crabtree-positive yeasts. However, little is known about its proteolytic capacity.…”
Section: Discussionmentioning
confidence: 92%
“…marxianus, an interesting yeast in biotechnology, has been regularly isolated from dairy products due to its ability to assimilate a wide range of sugars, such as lactose. Beniwal et al [49] reported K. marxianus 6C17 ability to hydrolyze galactose into ethanol, thus verifying its variability in sugar fermentation and thereby its alignment with Crabtree-positive yeasts. However, little is known about its proteolytic capacity.…”
Section: Discussionmentioning
confidence: 92%
“…Indeed, it has emerged that even a trait such as lactose utilisation, long considered one of the defining characteristics of K. marxianus , is not universal, and many strains exhibit very poor growth on lactose, a phenotype that was shown to be due to polymorphisms in the LAC12 gene, which encodes a permease responsible for transport of lactose into the cell (Varela et al, 2017 ). Although recent studies on sugar transport and physiology are starting to address the deficit (Fonseca et al, 2013 ; Signori et al, 2014 ; Beniwal et al, 2017 ; Dias et al, 2017 ; Diniz et al, 2017 ), it is true to say that a lot of the underlying knowledge about the biology of K. marxianus is based on inference of similarity with its sister species, Kluyveromyces lactis , which was developed as a model for studying lactose-positive yeasts since the 1960's (Fukuhara, 2006 ). The genome of K. lactis was sequenced more than a decade ago (Souciet et al, 2000 ), with a more recent functional reannotation and genome scale model that provides a deeper understanding of the core metabolism of this species (Dias et al, 2012 , 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…The relatively low degree of conversion is mainly caused by the superior stability of galactose, as reflected by these compounds’ equilibrium ratio (see above). However, the remaining galactose could simply be removed by a yeast treatment with Kluyveromyces marxianus ( Figure S1 ) [ 20 , 21 ]. This selective digestion of a 2-epimer by micro-organisms has already been demonstrated in the production of N -glycolylneuraminic acid [ 22 , 23 ].…”
Section: Resultsmentioning
confidence: 99%
“…To remove galactose from the mixture, Kluyveromyces marxianus was grown in 50 mL of medium (yeast extract, 10 g/L; peptone, 20 g/L; galactose, 20g/L) at 200 rpm and 30 °C until at least an OD600 of 6 was reached. This particular strain has the advantage of consuming galactose whereas a typical strain like Saccharomyces cerevisiae would not [ 20 , 21 ]. Moreover, the glycerol production is very low, even after long incubation periods.…”
Section: Methodsmentioning
confidence: 99%